2015
DOI: 10.32913/mic-ict-research.v3.n12.314
|View full text |Cite
|
Sign up to set email alerts
|

Robust Direction of Arrival Estimation Using Uniform Circular Antenna Array based on Total Forward - Backward Matrix Pencil Method

Abstract: In  this  paper,  we  propose  an  approach  to estimate  the  Direction  of  Arrival  (DOA)  of  Radio coherent  incoming  signals  using  the  Total  Forward  – Backward  Matrix  Pencil  algorithm  (TFBMP).  This algorithm  works  directly  on  samples  of  signals impinging  on  an  M  –  element  Uniform  Circular Antenna (UCA) array, which has a smaller size as well as  larger  observation  angle  in  comparison  with  the Uniform  Linear  Antenna  (ULA)  array.  Therefore,  the correlation  between  the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In addition, algorithms are often developed with the assumption that the number of incoming sources is known [5,8,9], which reduces the generality of the problem and is no longer true when applied in practice because the signal received at the antenna array is the total signal of many unknown and unstable incoming sources. Several recent publications have shown that machine learning methods have gradually been applied to solve the problem of DOA estimation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, algorithms are often developed with the assumption that the number of incoming sources is known [5,8,9], which reduces the generality of the problem and is no longer true when applied in practice because the signal received at the antenna array is the total signal of many unknown and unstable incoming sources. Several recent publications have shown that machine learning methods have gradually been applied to solve the problem of DOA estimation.…”
Section: Related Workmentioning
confidence: 99%
“…ese antenna elements operate in phase with each other to create a unique radiation direction so that the signal sent to the processor is kept in phase and amplitude in comparison with the incoming signal. Furthermore, the ULA antenna array has several advantages over other types of antenna arrays as shown in [3,9].…”
Section: Uniform Linear Antenna Array and Signal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques have been developed in the DOA estimation problem MUSIC [2]- [4], ESPRIT [5], TFBMP [6], [7]. In which, the MUSIC algorithm is an algorithm that has been developed for a long time and has many practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…These antennas operate in phase with each other to create a unique radiation direction so that the signal sent to the processor is kept in phase and amplitude in comparison with the signal arriving at the antenna system. Furthermore, the ULA antenna array has several advantages over other types of antenna arrays as shown in [1], [6].…”
Section: Introductionmentioning
confidence: 99%